INSTITUTIONAL LEADERSHIP AND JOB BURNOUT OF NEWLY QUALIFIED TEACHERS: THE MEDIATING AND MODERATING ROLE OF WORK ENGAGEMENT AND PROFESSIONAL DEVELOPMENT - Khutso Pitso Mankgele; Mahunele Thotse; Mpho Mokgaetji Chidi (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
Institutional leaders also play a vital role in providing resources and support to employees. By ensuring that employees have access to the necessary tools, training, and support. Leaders set the stage for employees to be successful in their roles. The present investigation attempts to determine the role of intuitional leadership (IL) in the job burnout (JB) of newly qualified teachers. This study also evaluates the mediating role of work engagement (WE) and moderating role of professional development (PD). This study tested the hypothesis using a partial least squares structural equation modelling (PLS-SEM) by applying smart PLS software. A total of 138 teachers from selected Districts in the Limpopo Province were targeted for data collection. The results confirmed that IL positively impacts JB. The results validate the mediating role of WE. The moderating results revealed that PD does not play a moderating role in proposed relationships. This study serves the existing body of literature by providing empirical evidence on the significance of IL.